Heterostemma tongbiguanense (Apocynaceae, Asclepiadoideae), a new species from Yunnan, China - Yang, Rong-Cong; Yin, Yi-Qiang; Yang, Zheng-Hua; Yin, Fa-Wang; Zhang, Yong-Sheng; Zhang, Yun-Hui; Zuo, An-Ru; Shen, Jian-Yong (Phytotaxa, 2026)
Heterostemma tongbiguanense (Apocynaceae), a new species from Yunnan Tongbiguan Provincial Nature Reserve, Yunnan Province, China, is described and illustrated. It is similar to H. cucphuongense T. B. Tran & Rodda and H. tanjorense Wight & Arn.; morphological differences are mainly in the stems and leaves with densely brown-yellow tomentose, corona apically serrated, below middle are papillae on both sides. Photographs, distribution, comparison with related species, and a conservation assessment are provided for this rarely observed species.